Sound dissipation by cylindrical pipelines of aviation systems in resilient medium - Шкварницкая, Т. Ю. (Proceedings of National Aviation University (archive), 1998)
Proposed here is a mathematical instrument for determination of spectre of signal which is echoed from the pipeline in the spring media. Calculated is the spectre of concrete conditions Comparison of rated and experimental data is introduced. It is shown that high sensitivity of spectre resonant frequency can be used for finding pipeline defects